Does Consumption of Baker's Yeast (Saccharomyces cerevisiae) by Black Soldier Fly (Diptera: Stratiomyidae) Larvae Affect Their Fatty Acid Composition?. Issue 3 (11th May 2021) - Opatovsky, Itai; Vitenberg, Tzach; Jonas-Levi, Adi; Gutman, Roee
Abstract: Fatty acids are important compounds for insects, but the requirements for essential fatty acids may differ between insect species. Most of the fatty acids are acquired through the insect's diet; therefore, supplementing the diet with baker's yeast ( Saccharomyces cerevisiae Meyen ex E.C. Hansen), which produces unsaturated fatty acids, was predicted to affect the fatty acid composition of the insect. The tested insect was the black soldier fly (BSF) ( Hermetia illucens L.), that is used as a source of protein and fat in feed. Therefore, there is importance for BSF larvae (BSFL) nutritional composition, especially the unsaturated fatty acids content, which is one of the nutritional limitations for mammalian diets. The dominant fatty acids of the tested BSFL were the saturated fatty acids: lauric, myristic, and palmitic acids, as found in other BSF studies. Oleic acid (c18:1) and linoleic acid (C18:2) were the abundant unsaturated fatty acids in the BSFL. The proportion of linoleic acid was higher in the substrate with the supplemental yeast; however, this did not affect its proportion in the larvae. The higher proportion of linoleic acid may have been exploited as a source for production of saturated lauric acid. Therefore, providing unsaturated fatty acids to the substrate through supplemental baker's yeast is not the most efficient way to increase the proportion of unsaturated fatty acids in the larvae.